Impacts of foreign direct investment on economic growth - PANN, Zun (KDI School, 2017)
This study analyzes the growth rate of Myanmar economic by inflow of foreign direct investment based on Vector Error Correction (VECM) Model. The objective of this paper is to determine whether getting foreign direct investment has positive or negative effects on the growth rate of GDP has positive or negative effects in the long-run. This study discovered that the growth rate of GDP is positively associated with getting foreign direct investment in the long-run but it is not statistically significant. Moreover, this study found that the negative correlation between the balance of trade and the gowth rate of GDP in the long-run, which owes to a trade deficit situation of Myanmar economy. Therefore, this study suggests that the government should focus on the economic stability and sound foreign direct investment policies to gain growth in Myanmar economy.
Thesis(Master) --KDI School:Master of Public Policy,2017